2010
DOI: 10.1104/pp.110.167254
|View full text |Cite
|
Sign up to set email alerts
|

Lignin Composition and Structure in Young versus AdultEucalyptus globulusPlants

Abstract: Lignin changes during plant growth were investigated in a selected Eucalyptus globulus clone. The lignin composition and structure were studied in situ by a new procedure enabling the acquisition of two-dimensional nuclear magnetic resonance (2D-NMR) spectra on wood gels formed in the NMR tube as well as by analytical pyrolysis-gas chromatography-mass spectrometry. In addition, milled-wood lignins were isolated and analyzed by 2D-NMR, pyrolysis-gas chromatography-mass spectrometry, and thioacidolysis. The data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
263
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 283 publications
(287 citation statements)
references
References 59 publications
19
263
2
3
Order By: Relevance
“…The values of soluble lignin observed for wood material (3.9% and 4.0%, Table 1) are comparable with the reported 3.6% (Pereira 1988) and are in the range of 4.4% to 8.1% (Poke et al 2006). The values of Klason lignin (21.4 % and 21.8 %) were observed to be in the range of 18.9% to 25.5% reported by Poke et al (2006) and near the reported 19.8% (Rencoret et al 2011). This relation between acid-insoluble and soluble lignin is similar for other hardwoods, i.e.…”
Section: Lignin Determination By Wet Chemistrysupporting
confidence: 73%
See 1 more Smart Citation
“…The values of soluble lignin observed for wood material (3.9% and 4.0%, Table 1) are comparable with the reported 3.6% (Pereira 1988) and are in the range of 4.4% to 8.1% (Poke et al 2006). The values of Klason lignin (21.4 % and 21.8 %) were observed to be in the range of 18.9% to 25.5% reported by Poke et al (2006) and near the reported 19.8% (Rencoret et al 2011). This relation between acid-insoluble and soluble lignin is similar for other hardwoods, i.e.…”
Section: Lignin Determination By Wet Chemistrysupporting
confidence: 73%
“…However, due to the higher extractives content in heartwood, when the total lignin is reported to original wood, the values are slightly different: 24.3% and 23.5%, respectively for sapwood and heartwood (Lourenço et al 2010). These are values in the range of values reported for E. globulus wood of 24.2% to 27.9% (Miranda and Pereira 2002b); 24.7% to 31.2% (Poke et al 2006); 25.4% (Ramírez et al 2009); or 24.5% (Rencoret et al 2011), while a somewhat lower value of 21.9% was reported by Patt et al (2006). It is known that such amplitude of values is due to different factors such as wood origin (Miranda and Pereira 2002b;Poke et al 2006) or age of the tree (Miranda and Pereira 2002c).…”
Section: Lignin Determination By Wet Chemistrymentioning
confidence: 75%
“…Based on these results and the mass spectral characteristics of VI , this compound appeared to have originated from β–5 structures (somehow related to V ) during thioacidolysis or desulfurization. The peak for this compound VI (Figure 2) was originally assigned to be a β–6 dimer but, because such coupling is chemically impossible, it was later suggested to be consistent with a β–1 isochroman structure 8b, 9a, 11. From MS analysis and the herein established derivation of compound VI from a β–5 dimeric model compound, it is now clear that the structure shown in Figure 1 and Figure S1 is simply derived from an unopened phenylcoumaran, as will be described more fully elsewhere.…”
mentioning
confidence: 99%
“…2 and 3, the HSQC NMR spectra of the lignin fractions exhibited aliphatic (C/H 10-40/0.5-2.5) and aromatic 13 C-1 H correlation regions (C/H 95-150/5.5-8.0). The main cross signals of the lignin fractions in the HSQC spectra are assigned in Table 5 according to previous reports (Rencoret et al 2011;Sun et al 2013).…”
Section: D-hsqc Nmr Spectramentioning
confidence: 99%
“…Likewise, the FA2 (C2-H2), FA8 (C8-H8), and FA7 (C7-H7) correlations were observed at δC/δH 111.0/7.28, 116.4/6.40, and 143.7/7.50. Based on the quantification methodology (Rencoret et al 2011;Sun et al 2013), the main substructures among the lignin fractions and their abundances were estimated quantitatively. As shown in Table 6, the ratio of S/G/H was used to estimate the difference of lignin fractions in different conditions.…”
Section: D-hsqc Nmr Spectramentioning
confidence: 99%